2004
DOI: 10.4321/s1699-65852004000100003
|View full text |Cite
|
Sign up to set email alerts
|

Halitosis de origen periodontal: revisión

Abstract: Privada con dedicación exclusiva a Periodoncia e Implantes dentales en Gijón.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(92 reference statements)
0
0
0
Order By: Relevance
“…Several authors have mentioned the relevance of evaluating these biomarkers in patients with periodontitis due to the alteration that occurs in their levels as the inflammatory process characteristic of periodontitis increases [23]. On the other hand, it has been suggested that volatile compounds such as ammonium, produced by bacterial metabolism, may be found to be increased in patients with periodontal pockets [24], likewise, the presence of blood may be associated with ulcerations of the gingival sulcus epithelium [25]. In this study, ammonium had to be excluded due to errors in the test strips of the first batch used, so this comparison was not made, but the literature recognizes the importance of the information that this biomarker could provide for the prediction of response to periodontal treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have mentioned the relevance of evaluating these biomarkers in patients with periodontitis due to the alteration that occurs in their levels as the inflammatory process characteristic of periodontitis increases [23]. On the other hand, it has been suggested that volatile compounds such as ammonium, produced by bacterial metabolism, may be found to be increased in patients with periodontal pockets [24], likewise, the presence of blood may be associated with ulcerations of the gingival sulcus epithelium [25]. In this study, ammonium had to be excluded due to errors in the test strips of the first batch used, so this comparison was not made, but the literature recognizes the importance of the information that this biomarker could provide for the prediction of response to periodontal treatment.…”
Section: Discussionmentioning
confidence: 99%